Reconciling the environmental implications of late Quaternary faunal and pollen records in southern Africa - Alexandra L. Norwood; John Rowan; J. Tyler Faith (Quaternary Science Advances)
Across southern Africa, the Pleistocene-Holocene transition was associated with changes in community composition of large mammalian herbivores, which included the extinction and extirpation of numerous grazers. Past research has often linked these changes to the contraction and disappearance of grasslands; however, the relationship between faunal and pollen records spanning this transition has not been systematically analyzed. Here, we investigate changes in fossil ungulate community composition and grass pollen abundance from late Quaternary sites across southern Africa to evaluate the extent to which these communities track paleovegetation change across this interval. Our dataset draws from faunal and pollen records across southern Africa. Results from the comparison of compositional changes in both records suggest a sub-continental-scale decoupling of grass cover and ungulate community composition during the Pleistocene-Holocene transition. Although there is strong evidence for a regional-scale decline in grazers from the Last Glacial-Interglacial Transition to the early Holocene, there is no evidence for regional-scale declines in grassy vegetation. Several potential mechanisms may account for this decoupling of grazers and grass abundance. The possible strengthening of winter rainfall systems during glacial Pleistocene may have played a role by enhancing year-round availability of grasses in the interior and by elevating moisture availability and productivity in the Cape Floristic Region. Alternatively, current paleoecological data allow for the possibility that Pleistocene ‘grazers’ consumed more dicots, such that their decline at the onset of the Holocene reflects dietary niche contraction rather than vegetation change. These findings contribute to a growing body of evidence challenging the link between grass abundance and grazer diversity and complicate our understanding of the drivers of late Quaternary extinctions in southern Africa.